(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Effective communication in the classroom goes beyond vocabulary and grammar; it involves how speech is delivered. Intonation and word stress are critical prosodic features of spoken English that shape meaning, indicate speaker intention, and affect student comprehension. This paper explores the pedagogical importance of these features in the context of teaching English as a foreign language (EFL). Drawing on linguistic theory and classroom-based studies, we examine how intonation and word stress enhance speech clarity, support meaning-making, and influence student engagement. The paper also recommends strategies for integrating intonation and stress training into teacher education programs to improve oral instruction.